Unlocking Pakistan's Revenue Potential - Cevik, Serhan (Washington, D.C. : International Monetary Fund, 2016)
Despite the significant progress in recent years, Pakistan's tax revenue remains low relative to comparator countries and the tax effort expected for the country's level of development. In light of the potential endogenity of tax revenue and economic growth, this paper contributes to the literature by developing a novel identification strategy to estimate the short-run and long-run elasticities of tax revenue. The empirical findings indicate that a tax system with low elasticity cannot take full advantage of economic growth. Accordingly, unlocking revenue potential is dependent on broadening the tax base, strengthening administration, and rationalizing tax policy across all levels of the general government.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet